2023
DOI: 10.1021/acs.inorgchem.3c01646
|View full text |Cite
|
Sign up to set email alerts
|

Five Porous Complexes Constructed from a Racemic Ligand: Synthesis, Chiral Self-Assembly, Iodine Adsorption, and Desorption Properties

Abstract: Herein, a chiral bispyridyl ligand (L) was designed and synthesized using a Schiff base condensation reaction, followed by a 1,3-H shift. Five complexes, [Zn2 L 2(OAc)4] (1), {[CdLCl2(DMF)]·4H2O} n (2), [Cd2 L 2I4]·4H2O (3), {[CdL 2(H2O)2]­(NO3)2·2CH3OH} n (4), and [Hg2 L 2Cl4]·2DMF (5), were synthesized and characterized upon its reaction with Zn­(II), Cd­(II), or Hg­(II) ions, respectively. X-ray crystallography shows that the organic compound exists as a racemic ligand with equal amounts of its R- and S-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…The effect of the anions on the structures of complexes 1 – 4 may be attributed to the following three reasons: (i) the versatile coordination geometry of Cd­(II) ions results in diverse coordination polymers that are very sensitive to the synthesis conditions; (ii) the different shape, size, and coordination ability of the anions play an important role in the coordination structures; and (iii) noncovalent interactions, such as hydrogen bonds, π···π stacking interactions, and van der Waals forces, also contribute to the different topological structures. In addition, it is noteworthy that all of the complexes derived from the racemic ligand are heterochiral assemblies instead of homochiral assemblies during the formation of the polymeric structures, which are consistent with our previous work …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The effect of the anions on the structures of complexes 1 – 4 may be attributed to the following three reasons: (i) the versatile coordination geometry of Cd­(II) ions results in diverse coordination polymers that are very sensitive to the synthesis conditions; (ii) the different shape, size, and coordination ability of the anions play an important role in the coordination structures; and (iii) noncovalent interactions, such as hydrogen bonds, π···π stacking interactions, and van der Waals forces, also contribute to the different topological structures. In addition, it is noteworthy that all of the complexes derived from the racemic ligand are heterochiral assemblies instead of homochiral assemblies during the formation of the polymeric structures, which are consistent with our previous work …”
Section: Resultssupporting
confidence: 92%
“…In addition, it is noteworthy that all of the complexes derived from the racemic ligand are heterochiral assemblies instead of homochiral assemblies during the formation of the polymeric structures, which are consistent with our previous work. 55 3.3. PXRD and TGA.…”
Section: Influencing Factors For Self-assemblymentioning
confidence: 99%
“…After the desorption of methanol, these characteristic peaks disappeared, and the IR spectra of 3 @MeOH-des were consistent with those of CP 3 , implying that the methanol molecules could be completely desorbed from 3 @MeOH-ads, and CP 3 remained stable during the adsorption–desorption process. The results of PXRD patterns showed that the characteristic peaks of CP 3 did not change obviously after the vapor adsorption, indicating that the lattice structure of CP 3 was not affected by the noncovalent interactions between the methanol molecules and CP 3 in adsorption–desorption process . Similarly, it was found that the PXRD patterns of CP 3 hardly changed during the adsorption/desorption process, which further confirmed the stability of the crystalline solid sample.…”
Section: Resultsmentioning
confidence: 99%
“…The results of PXRD patterns showed that the characteristic peaks of CP 3 did not change obviously after the vapor adsorption, indicating that the lattice structure of CP 3 was not affected by the noncovalent interactions between the methanol molecules and CP 3 in adsorption−desorption process. 68 Similarly, it was found that the PXRD patterns of CP 3 hardly changed during the adsorption/desorption process, which further confirmed the stability of the crystalline solid sample. CP 5 and 6 were characterized via the same method, and the results also showed that both CPs were structurally stable during the experiments.…”
Section: Recyclable Adsorption Experimentsmentioning
confidence: 99%
“…Schiff base metal complexes as reaction catalysts and solid-state physical properties (materials science) have been transferred to (3) and ( 7), respectively. The molecular design of organic ligands is important for the adsorption of gas molecules onto porous metal-organic complexes [11] and magnetic complexes [12] that respond external fields, and the ease of synthesis of Schiff bases is utilized. (Actually, the cited references in this short text are limited to journals that can be viewed at the author's affiliated institution.)…”
Section: (4) Schiff Base Ligands In Metal Complexesmentioning
confidence: 99%